Student perspectives on factors that influence the implementation of evidence-based practice in occupational therapy. Issue 4 (22nd December 2021) - Hitch, Danielle; Nicola-Richmond, Kelli; Richards, Kieva; Stefaniak, Rachel
ABSTRACT: Aim: Evidence-based practice (EBP) is perceived as an integral component of contemporary allied health practice. While allied health clinicians (such as occupational therapists) have generally positive attitudes towards EBP, research suggests that they find its implementation consistently challenging. The professional literature increasingly suggests that more effective EBP learning takes place when social constructivist approaches to learning are adopted. The authors of this study sought to use the pre-existing knowledge and perceptions of occupational therapy students to inform a curriculum review of an EBP unit. Therefore, the aim of this content analysis study was to investigate how occupational therapy students perceive and critically analyse factors that influence the implementation of EBP, specifically strengths, weaknesses, opportunities and threats (SWOT). Methods: The study sampled students in the third year of a 4-year, Bachelor level Australian Occupational Therapy Program. The students were undertaking the first of two EBP units, and data were collected from the first assignment they submitted for these units. The assignment required the students to complete a SWOT analysis of EBP in occupational therapy, and response to a statement around whether it should be mandatory. Data were collected over 2 consecutive years from a total of 64 occupational therapy students. All data collected were subjected to content analysis, with themes identified by at least 25% of students in each cohort retained for analysis and formation into overall themes. Results: Participating occupational therapy students identified five strengths, four weaknesses, six threats but only one opportunity for EBP. Three key themes were identified within the data: first, the role and purpose of EBP; second, the resources it requires and third, factors that influence its success. The students perceived the main purpose of EBP as supporting positive practice change, and highlighted its roles in building clinician capacity and professional credibility. They also characterized EBP as a separate and specialist practice that requires specific training and resourcing to achieve, and questioned its feasibility as an integrated part of daily practice. Along with previously identified challenges around time and resourcing, the students also highlighted negative attitudes and beliefs from senior colleagues as an important negative influence on the success of EBP. Conclusion: The current study consolidates a growing body of international literature about the value of social constructive approaches to EBP in undergraduate education. Vertical constructive alignment that embeds EBP through undergraduate education, rather than the provision of 'EBP'-specific units, should now be considered best practice. However, this embedded approach requires the explicit and repeated communication of the presence of EBP in all learning opportunities, to enable students to recognize opportunities to deploy their existing knowledge and skills.